Pengaruh Model Pembelajaran dan Koordinasi terhadap Kemampuan Shooting Bola Basket - Rellya Runasari; Isdaryono Isdaryono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This aim of research to: 1) the impact of individual learning model and group learning model towards basketball shooting skill, (2) high coordination impact and low coordination towards basketball shooting, and (3) learning interaction model and coordination basketball shooting skill. The research populations are 44 basketball students club in SMA Negeri 2 Bandar Lampung. The research samples are 24 students with purposive sampling. All of the data in this research is taken by test and measurement towards coordination of throw and catch test also the result of shooting with shooting skill test of basketball. The data analysis technique used is the variant analysis ANOVA. The result of this research shows: (1) there is an individual learning model and group learning model towards basketball shooting, (2) there is high influence and low influence towards shooting skill on basketball, and (3) there is interaction learning model and coordination over shooting skill on basketball. Keywords: Learning Model, Coordination, Basketball, The Result of Shootin